2018
DOI: 10.1002/zaac.201800096
|View full text |Cite
|
Sign up to set email alerts
|

Triphenylphosphane Oxide Complexes of Lanthanide Nitrates: Polymorphs and Photophysics

Abstract: A series of mer‐[Ln(NO3)3(Ph3PO)3] complexes were prepared from Ln(NO3)3·xH2O and Ph3PO in chloroform (Ln = La, Nd, Sm, Eu, Gd, Tb, Dy, and Er). The La and Nd complexes were 0.25 CHCl3 solvates, whereas the others were solvent‐free. The identical reaction using Yb(NO3)3·xH2O produced the unique salt trans‐[Yb(NO3)2(Ph3PO)4][Yb(NO3)4(Ph3PO)]·Et2O. All nitrate ions in all complexes are η2‐chelating. A comparison of the various [Ln(NO3)3(Ph3PO)3] structures, including those in the literature, reveals at least fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The intensity of the emission in the PL spectra was normalized at 593 nm, which was derived from the magnetic dipole transition ( 5 D 0 → 7 F 1 ). Considering a previous report on the optical properties of [Eu­(Ph 3 PO) 3 (NO 3 ) 3 ], we assigned an excitation band between 250 and 300 nm to the excitation of antenna ligands, where strong peaks were observed in the diffuse reflection spectra (Figure b) . The PL spectra suggested that the intensity ratio ( I ED / I MD ) of the emission maxima of the electric dipole transition (618 nm) and magnetic dipole transition (593 nm) for 1-a was larger than that for 2-a .…”
Section: Results and Discussionmentioning
confidence: 77%
“…The intensity of the emission in the PL spectra was normalized at 593 nm, which was derived from the magnetic dipole transition ( 5 D 0 → 7 F 1 ). Considering a previous report on the optical properties of [Eu­(Ph 3 PO) 3 (NO 3 ) 3 ], we assigned an excitation band between 250 and 300 nm to the excitation of antenna ligands, where strong peaks were observed in the diffuse reflection spectra (Figure b) . The PL spectra suggested that the intensity ratio ( I ED / I MD ) of the emission maxima of the electric dipole transition (618 nm) and magnetic dipole transition (593 nm) for 1-a was larger than that for 2-a .…”
Section: Results and Discussionmentioning
confidence: 77%
“…White crystalline products were precipitated from these solutions upon addition of ethyl ether. In contrast to Ph 3 PO complexes, which in almost all cases form mer ‐[ Ln (NO 3 ) 3 (Ph 3 PO) 3 ], the Ph 3 AsO products precipitated from CHCl 3 seemed to favor trans ‐[ Ln (NO 3 ) 2 (Ph 3 AsO) 4 ]NO 3 ( 1 ) ( Ln = Y, Eu, Tb, Dy) over mer ‐[ Ln (NO 3 ) 3 (Ph 3 AsO) 3 ] ( 2 ) ( Ln = Sm) species, as determined via elemental analysis (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Amongst the three meridional nitrate ligands, an “outer” nitrate lies in the meridional plane of the molecule, while the center and remaining outer nitrate planes are coplanar with the axial Ph 3 AsO– Ln –OAsPh 3 vector. Both arrangements 1 and 2 have been observed in the better‐studied Ph 3 PO‐ Ln complexes, but 2 is by far the more commonly observed, with 1 having been noted only for Ln = Dy and Lu,, and in the unusual trans ‐[Yb(NO 3 ) 2 (Ph 3 PO) 4 ][Yb(NO 3 ) 4 (Ph 3 PO)] · Et 2 O …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both compounds emit green (CIE: 0.3149, 0.5789, Figure 3c) and greenish-yellow luminescence (CIE: 0.4089, 0.5344, Figure 3c), with narrow emission bands in 450-650 nm. [25,32] The maximum intensities at 489, 543, 586, and 620 nm are assigned to the 5 D 4 ! 7 F J (J = 3-6) transitions of Tb 3 + (Figure 3a, 3b).…”
Section: Luminescence Propertiesmentioning
confidence: 99%